2008
DOI: 10.2174/1874940200801010072
|View full text |Cite
|
Sign up to set email alerts
|

Sphingolipid Metabolism Inhibitors and Cell Function

Abstract: It has been widely shown that ceramide, ceramide phosphate, sphingosine and sphingosine-1-phosphate are molecules involved in cell proliferation, differentiation and apoptosis. The regulation of the enzymes that control their metabolism has an important role for cellular fate. Many studies in the field have shed light on sphingolipid metabolism inhibition and on its role in cell processes such as gene expression, DNA duplication and RNA transcription. The aim of this review is to collect, in a systematic way, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 98 publications
0
8
0
Order By: Relevance
“…In OVCAR-8 human ovarian cancer cells, GCS upregulation has been reported to result in a significant increase in the levels of cSrc-and b-catenin signaling and also in a significant decrease in intracellular paclitaxel levels, showing increased activity of P-gp. In contrast, downregulation of GCS causes suppression of these signaling molecules and also of P-gp [64].…”
Section: Glucosylceramide Synthase In Drug Resistancementioning
confidence: 93%
See 1 more Smart Citation
“…In OVCAR-8 human ovarian cancer cells, GCS upregulation has been reported to result in a significant increase in the levels of cSrc-and b-catenin signaling and also in a significant decrease in intracellular paclitaxel levels, showing increased activity of P-gp. In contrast, downregulation of GCS causes suppression of these signaling molecules and also of P-gp [64].…”
Section: Glucosylceramide Synthase In Drug Resistancementioning
confidence: 93%
“…The imino sugar OGT2378 that is also an inhibitor of GCS reduced the tumorigenic capability of MEB4 melanoma cells [80]. It has been shown that GCS is overexpressed in many multidrug-resistant cancer cell lines in leukemia, breast cancer, and renal cell cancer [64]. Treatment of various kinds of cancer cells with several GCS inhibitors affects basic cellular functions such as growth, death, and adhesion.…”
Section: Glucosylceramide Synthase In Cancer Therapymentioning
confidence: 99%
“…The above data have been obtained mostly from model membrane studies. Investigations at the cellular level have allowed to assign a wide variety of functions to SL, including apoptosis, cell growth, cell membrane function, tumor formation, drug resistance, degranulation, and phagocytosis, among others [15][16][17][18] . Alterations in the normal activities of SM-cycle enzymes have been linked to many central nervous system-related pathologies such as Alzheimer's, Parkinson's, ischemia/hypoxia, depression, schizophrenia or Niemann-Pick diseases 19 .Specific SL functions have often been characterized in cells with decreased amounts of SL, using either SL-degrading enzymes (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Alterations in the normal activities of SM-cycle enzymes have been linked to many central nervous system-related pathologies such as Alzheimer's, Parkinson's, ischemia/hypoxia, depression, schizophrenia or Niemann-Pick diseases 19 .Specific SL functions have often been characterized in cells with decreased amounts of SL, using either SL-degrading enzymes (e.g. sphingomyelinases or ceramidases) 20 , or specific enzyme inhibitors 15,[21][22][23] , of which the SPT inhibitor myriocin is a good example [24][25][26][27] . Procedures to decrease the SL contents of cells constitute good tools to determine their potential functions in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…As complex lipids - in contrast to FAs - may not be easily available for rescue, enzyme inhibitors can be used to evaluate whether they copy the phenotype of interest. Many small-molecule inhibitors have been developed to modify lipid biosynthetic enzyme activities 2125 (Tables 1, 2). For example, inhibitors of serine palmitoyltransferase include sphingofungins, lipoxamycin and myriocin.…”
Section: Introductionmentioning
confidence: 99%